Evaluation of in vitro antidiabetic mechanisms of methanolic extracts from four Ficus deltoidea jack varieties - Yahaya, Nurshieren (2020)
Diabetes Mellitus has been a global metabolic disorder and affected people of various ages. In this research, four varieties of methanolic Ficus deltoidea extracts containing natural products that possess anti-diabetic properties has been studied. The study was carried out because antidiabetic synthetic drugs have been reported to have negative side effects on diabetes patients. Therefore, the study was done to elucidate insulin-secreting activity towards the beta pancreatic cell, to elucidate glucose uptake activity in insulin targeted cells, to determine the potential of insulin-sensitizing activity in adipocytes cells and to determine the potential of antiglycation activities of four methanolic Ficus deltoidea varieties. The viability study which manifests viability assay has shown that methanolic Ficus deltoidea variety deltoidea, angustifolia and motleyana does not toxic towards the treated cells with the highest viability were portrayed by the highest viability can be seen when treated with 500 μg/ml of methanolic extract Ficus deltoidea variety angustifolia with 151.42 ± 0.08 percent (p<0.001) on beta pancreatic cell, 1000 μg/ml of methanolic extract Ficus deltoidea variety angustifolia with 122.66 ± 1.92 percent (p<0.01) on L6 muscle cell and the highest viability can be seen at 100 μg/ml when treated with methanolic Ficus deltoidea variety motleyana at 110.58 ± 3.45 percent on 3T3F442A adipocytes cell but not significant. Besides, insulin secretion study conducted with insulin secretion assay showed methanolic extracts of Ficus deltoidea varieties can stimulate insulin release from pancreatic cells through the KATP independent pathway. The highest insulin secretion was shown by methanolic extract Ficus deltoidea variety deltoidea with 6.24 fold (p<0.001). In addition, the extracts able to stimulate glucose uptake in basal and insulin-mediated state where the highest uptake can be seen in insulin-mediated state of L6 muscle cell treated with methanolic extract Ficus deltoidea variety motleyana with 3.65 fold (p<0.001) when compared to control and 2.90 fold (p<0.001) when compared to insulin 100 nM. Apart from that the highest uptake can be seen in insulin-mediated state of 3T3F442A adipocyte cell treated with methanolic extract Ficus deltoidea variety motleyana with 1.39 fold (p<0.001) when compared to control and 1.27 fold (p<0.001) when compared to insulin 100 nM. All of the extracts follow the phosphatidylinositol-3-kinase-independent pathway except for Ficus deltoidea variety motleyana where when treated to 3T3F442A cell, the extract does not follow both of phosphatidylinositol-3-kinase-dependent and independent pathway. While in gene expression study through using Quantigene assay kit, showed methanolic Ficus deltoidea variety bilobata as the highest expression for phosphatidylinositol-3-kinase-dependent pathway with 1.24 fold in 6 hours while Ficus deltoidea variety motleyana showed the highest expression for phosphatidylinositol-3- kinase-independent pathway with 1.21 fold in 6 hours. All four varieties at a concentration of 100 μM in insulin-mediated state shown a significant glucose uptake activity in insulin resistance cell with the best secretion of leptin and inhibition of tumor necrosis factor-α was significantly recorded by methanolic extract Ficus deltoidea variety angustifolia with 2.56 fold (p<0.001) and 0.73 fold (p<0.001). Last but not least, the highest antiglycation activity was exhibited by methanolic Ficus deltoidea variety bilobata with 78.92 percent of advanced glycation endproducts inhibition formation along with the highest detection of fructosamine inhibition with 86.40 percent reduction. While Ficus deltoidea variety deltoidea showed significant results with protein thiol preservation of 6.14 fold (p<0.001) and protein carbonyl reduction with 1.76 fold (p<0.001). Total phenolic content assay showed that methanolic Ficus deltoidea variety bilobata to have highest phenolic content of 299.78 ± 2.88 mg GAE/ g of extract (p<0.001). The varieties also showed significant antioxidant activities. In conclusion, methanolic Ficus deltoidea extract showed that most extract follow independently of ATP-sensitive potassium channel in insulin secretion activity. Apart from that, the extracts follow glucose uptake phosphatidylinositol-3-kinase independent pathway, able to sensitize insulin and inhibit advanced glycation formation. Therefore, it is suggested that methanolic Ficus deltoidea extracts can be a promising candidate to be used as phytopharmaceutical agents to manage diabetes mellitus.